2020
DOI: 10.1128/mbio.00208-20
|View full text |Cite|
|
Sign up to set email alerts
|

Recognition Patterns of the C1/C2 Epitopes Involved in Fc-Mediated Response in HIV-1 Natural Infection and the RV114 Vaccine Trial

Abstract: Antibodies (Abs) specific for CD4-induced envelope (Env) epitopes within constant region 1 and 2 (C1/C2) were induced in the RV144 vaccine trial, where antibody-dependent cellular cytotoxicity (ADCC) correlated with reduced risk of HIV-1 infection. We combined X-ray crystallography and fluorescence resonance energy transfer-fluorescence correlation spectroscopy to describe the molecular basis for epitopes of seven RV144 Abs and compared them to A32 and C11, C1/C2 Abs induced in HIV infection. Our data indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
(114 reference statements)
1
5
1
Order By: Relevance
“…A series of recent studies using LucR.T2A IMCs have hypothesized that Vpu can compensate for the absence of Nef expression by fully downregulating cell-surface CD4 (93)(94)(95)(96)(97). Our results show that this is not the case.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…A series of recent studies using LucR.T2A IMCs have hypothesized that Vpu can compensate for the absence of Nef expression by fully downregulating cell-surface CD4 (93)(94)(95)(96)(97). Our results show that this is not the case.…”
Section: Discussioncontrasting
confidence: 61%
“…Infectious molecular clones encoding for the Renilla luciferase (LucR) reporter gene upstream of the nef sequence, and a T2A ribosome-skipping peptide to drive Nef expression are widely employed to quantify anti-HIV-1 ADCC responses (81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). Despite evidence that Nef-mediated CD4 downregulation is impaired when using these IMCs (54,79), a series of recent studies have hypothesized that Vpu can compensate for the absence of Nef expression and completely downregulate CD4 on its own (93)(94)(95)(96)(97). To evaluate this hypothesis, we used our intracellular staining to measure Nef and Vpu expression levels and study their impact on ADCC responses mediated by nnAbs against cells infected with IMC-LucR.T2A constructs.…”
Section: Impaired Nef Expression From Imc Lucrt2a Constructs Enhance the Susceptibility Of Infected Cells To Adccmentioning
confidence: 99%
“…Sera from RV305 subjects were capable of effective ADCC with increased potency and breadth compared to C1/C2 mAbs isolated from RV144 subjects [ 48 , 49 ]. Our structural analyses RV144 and RV305 mAbs confirmed their Cluster A specificity [ 50 ].…”
Section: Introductionsupporting
confidence: 55%
“…Relative fluorescence antibody dependent cellular cytotoxicity assays were carried out as previously described, with minor adjustments [ 50 , 52 , 53 ]. Briefly, EGFP-CEM-NKR-CCR5SNAP cells were coated with one of three antigen targets: gp120 93TH057 core, full-length gp120 93TH057 or gp120 BaL , all at 50 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…We recently developed an immunogen referred to as inner domain 2 (ID2), which stably expresses the conformational Cluster A epitope target within a minimal structural unit of gp120 [ 26 ]. Immunization studies in BALB/c mice with ID2 demonstrated that ID2 was highly immunogenic and that the Cluster A-specific responses were induced at levels that provided potent Fc-effector activities, including ADCC [ 27 , 28 , 29 , 30 ]. Here, we describe the engineering, functional analyses and immunogenicity of ID2-V1V2, an immunogen variant that incorporates both the Cluster A and V1V2 regions of HIV-1 Env to induce Fc-effector function responses to both epitope targets implicated in the protective effect of the RV144 vaccine trial.…”
Section: Introductionmentioning
confidence: 99%